2012
DOI: 10.1007/s00106-012-2642-7
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen von Rauschsignalen für die akustische Tinnitustherapie

Abstract: The higher spontaneous acceptance of natural sounds as compared to white noise appears not to be due solely to physical sound properties, but rather to result primarily from psychological factors. It may be possible to improve sound acceptance in tinnitus sound therapy by using signals with low amounts of dynamics and implementing the use of natural sounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Davis et al (2007) observed more consistent benefit over 12 months if Neuromonics Tinnitus Treatment involved masking of tinnitus for the first 2 months followed by intermittent perception of tinnitus compared to where there is intermittent perception of tinnitus throughout treatment. It may be useful to run future trials in which the temporal structure of sounds are changed often to maintain novelty and prevent sound adaptation, continuity illusion, and facilitate AL shifts toward external sound (Schreitmüller et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Davis et al (2007) observed more consistent benefit over 12 months if Neuromonics Tinnitus Treatment involved masking of tinnitus for the first 2 months followed by intermittent perception of tinnitus compared to where there is intermittent perception of tinnitus throughout treatment. It may be useful to run future trials in which the temporal structure of sounds are changed often to maintain novelty and prevent sound adaptation, continuity illusion, and facilitate AL shifts toward external sound (Schreitmüller et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The results of this study would agree with these suggestions, although we believe the process of tinnitus adaptation is more complex than habituation (Searchfield et al, 2012). Also, considering the BBN had a stronger effect on adaptation level while nature sounds influence residual emotion pathways, and nature sounds are more accepted (Schreitmüller et al, 2013), another clinical application would be the combing the two sounds or staging their use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original article, the citation for the text in the final paragraph under Discussion, Sound Adaptation as a Confound, “Changed often to maintain novelty and prevent sound adaptation, continuity illusion, and facilitate AL shifts toward external sound” was incorrectly cited as (Schreitmüller et al, 2013). It should be (Searchfield et al, 2012).…”
mentioning
confidence: 99%